If on a winter's night a traveler - Calvino, Italo (New York : Harcourt Brace Jovanovich, 1982)
Calvino shows that the novel, far from being a dead form, is capable of endless mutations. If on a winter$1 (Bs night a traveler turns out to be not one novel but ten, each with a different plot, style, ambience, and author.s
Translation of: Se una notte d'inverno un viaggiatore.
"A Helen and Kurt Wolff book."
Keywords: Italy -- Social life and customs -- Fiction